The impacts of energy supply and environmental taxation on carbon intensity - Máté, Domicián; Török, László; Kiss, Judit T. (Technological and Economic Development of Economy, 2023)
Carbon dioxide (CO2) is a significant source of Greenhouse Gas (GHG) emissions and plays a crucial role in climate change and global warming. This study aims to explain the effects of primary and renewable energy supplies and environmental taxation and to analyse how taxation can alter their direct effects on carbon intensity. The research was conducted using a generalized method of moments model that uses instrumental variables with two-stage (2SGMM) estimators to calculate the direct and moderating effects of environmental taxes on carbon intensity. This study confirms the EKC theorem, and results have shown that primary energy supply and environmental-related taxation positively contribute to carbon intensity. The second finding indicates that a major increase in the proportion of renewable energy will greatly slow the rate of carbon dioxide emissions. The study provides additional evidence concerning the moderating role of taxation in amplifying the impacts of primary and renewable energy supply. The empirical findings suggest that the taxation impact is more fiscal than an incentive. In addition to the current energy and economic crisis, considerable funding and fiscal policies are needed to achieve more sustainable development paths towards carbon neutrality and energy security.First published online 17 May 2023